2018
DOI: 10.1038/s41467-018-04995-y
|View full text |Cite
|
Sign up to set email alerts
|

Possible nitrogen fertilization of the early Earth Ocean by microbial continental ecosystems

Abstract: While significant efforts have been invested in reconstructing the early evolution of the Earth’s atmosphere–ocean–biosphere biogeochemical nitrogen cycle, the potential role of an early continental contribution by a terrestrial, microbial phototrophic biosphere has been largely overlooked. By transposing to the Archean nitrogen fluxes of modern topsoil communities known as biological soil crusts (terrestrial analogs of microbial mats), whose ancestors might have existed as far back as 3.2 Ga ago, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…This assumption is consistent with studies suggesting that continental colonization by microbial communities may have triggered oxidative weathering on continental surfaces prior to the Great Oxidation Event (e.g., Lalonde and Konhauser, 2015;Havig et al, 2019). Early life on land would have also enhanced the delivery of nutrients to the oceans such as fixed nitrogen (Thomazo et al, 2018) and would have increased the productivity of Paleoarchean shelfs and coastal margin environments (Lyons et al, 2014). Cyanobacterial land-based modern ecosystems may therefore hold keys in understanding how Earth's early terrestrial biogeochemical cycles were established and how they were linked to biogeochemical cycling in the marine environment.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This assumption is consistent with studies suggesting that continental colonization by microbial communities may have triggered oxidative weathering on continental surfaces prior to the Great Oxidation Event (e.g., Lalonde and Konhauser, 2015;Havig et al, 2019). Early life on land would have also enhanced the delivery of nutrients to the oceans such as fixed nitrogen (Thomazo et al, 2018) and would have increased the productivity of Paleoarchean shelfs and coastal margin environments (Lyons et al, 2014). Cyanobacterial land-based modern ecosystems may therefore hold keys in understanding how Earth's early terrestrial biogeochemical cycles were established and how they were linked to biogeochemical cycling in the marine environment.…”
Section: Discussionsupporting
confidence: 88%
“…However, later findings showed that sulfur vapor and hydrocarbon smog in the primitive ozone-free atmosphere may have strongly attenuated UV radiation (Kasting et al, 1989), and that the Archean landmasses could have been provided sufficient refugia to early photosynthesizers even under high UV fluxes (Garcia-Pichel, 1998). From a theoretical perspective, a continental * microbial phototrophic biosphere could have therefore existed early, before the Great Oxidation Event (Beraldi-Campesi et al, 2009;Lalonde and Konhauser, 2015), and have colonized emergent land surfaces (Thomazo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological fixation thus remains a necessity for continued growth. Fixed atmospheric C and N [20,22,23], along with other elements [24] can then be exported to underlying soils, improving landscape soil fertility. Because drylands cover nearly 45% of the total Earth continental area [25], and aridity is predicted to increase due to global warming [26][27][28], this N export activity of biocrusts matters not only locally, but also globally.…”
Section: Introductionmentioning
confidence: 99%
“…This microbial mantle provides ecosystem services such as protection from wind (Belnap & Gillette ; Zhang et al ) and water erosion (Gaskin & Gardner ). Biocrusts also contribute to soil fertility by fixing atmospheric carbon (Elbert et al ; Sancho et al ) and nitrogen (Barger et al ), by exporting significant proportions of both C and N, but also other elements to the soils they cover (Thiet et al ; Johnson et al ; Beraldi‐Campesi et al ; Thomazo et al ), and by trapping dust particles (Reynolds et al ). Unfortunately, biocrusts are very susceptible to trampling associated with human activities (Belnap & Eldridge ; Zaady et al ).…”
Section: Introductionmentioning
confidence: 99%